Auswirkung einer intensiven Ausdauerbelastung auf die Konsolidierung motorischer Gedächtnisinhalte: Ergebnisse einer Pilotstudie - Lehmann, N. (Leipziger Sportwissenschaftliche Beiträge, 2013)
This study investigates the effectiveness of acute, high intensive endurance exercises on motor skill learning. It is well established that motor memory traces are in a labile state immediately after encoding and retrieval. Furthermore, acute, high intensive bouts of exercise promote neuroplasticity and cognitive function in humans. The central idea of the study is to harness exerciseinduced neuroplasticity to improve the (re-)stabilization of motor memory traces. In this randomized, controlled study, subjects were instructed to perform a whole body balancing task on the stabilometer for a period of two consecutive weeks. The initial results suggest beneficial effects of acute, high intensive bouts of exercise on motor skill learning.